The Influence of Advertising, Sales Promotion and Personal Selling Toward Purchasing Decision to Hotel Stay in East Java - Dina Mayasari Soeswoyo; Choiri Amalia (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify the effect of advertising, sales promotion and personal selling on the decision of guests to stay at a hotel in East Java. Data was collected through questionnaires, observation, documentation and literature review from March to July 2022. Data were analyzed quantitatively using multiple and simple linear regression techniques. The results showed that simultaneously, advertising, sales promotion and personal selling have a significant effect on purchasing decisions. However, partially, the Sales promotion variable has no significant effect, while Advertising and Personal Selling have a significant effect on the guest's decision to stay at Hotel Ilona.